2006
DOI: 10.1002/pen.20608
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline spherulitic growth kinetics during shear for linear low-density polyethylene

Abstract: The Linkam shearing cell was used in conjunction with a polarized light microscope to study the isothermal crystallization process of linear low‐density polyethylene resins under simple shear flow. The growth of spherulitic morphology was observed under slow shear rates (less than 1 s−1). The crystalline spherulitic growth rate increases, as the shear rate increases. This has been attributed to the decrease of the activation diffusion energy. A relationship between the activation diffusion energy and the shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The effect of flow on the kinetics of crystallization was studied previously . In particular, Coccorullo et al used optical microscopy to determine nucleation and growth rate of iPP under weak shear deformation ( γ˙ = 0−0.3 s −1 ) using the Linkam shearing cell (CSS 450).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of flow on the kinetics of crystallization was studied previously . In particular, Coccorullo et al used optical microscopy to determine nucleation and growth rate of iPP under weak shear deformation ( γ˙ = 0−0.3 s −1 ) using the Linkam shearing cell (CSS 450).…”
Section: Introductionmentioning
confidence: 99%
“…1,[7][8][9][10][11][12][13][14][15][16][17] The effect of flow on the kinetics of crystallization was studied previously. [18][19][20][21][22][23][24][25][26][27] In particular, Coccorullo et al 23 used optical microscopy to determine nucleation and growth rate of iPP under weak shear deformation (_ c 5 020.3 s 21 ) using the Linkam shearing cell (CSS 450). It was reported that both the nucleation and growth rates increase exponentially as shear deformation is increased.…”
mentioning
confidence: 99%
“…It can be speculated that owing to relatively high blending temperature, the degradation of DMDHT would also be possible in addition to localization of this constituent between clay galleries. It should be noted once again that the extent of interfacial adhesion and range of fluctuations in shear thinning exponent of polymer=clay systems greatly depends on the type of polymers used [42,44] .…”
Section: Results and Discussion Analysis Of Clay Dispersionmentioning
confidence: 99%
“…A considerable increase in this parameter can be observed after melt processing of neat PE. This behavior known as shear induced crystallization involves accelerated nucleation and growth [44] . In other words, processed PE chains tend to have more ordered melt structure leading to a fall in free energy difference between melt and crystalline domains that facilitates nucleation process.…”
Section: Results and Discussion Analysis Of Clay Dispersionmentioning
confidence: 99%
“…The formation of oriented structures after the application of the shear can even allow a further improvement of the properties. [1][2][3][4] The effects of flow rate on the crystallization behaviors of polymers is largely studied for selected polymers, such as polyethylene (PE) and isotactic polypropylene (iPP) that present a drastic enhancement of the crystallization kinetics because of the flow field, whose main effect is mainly a faster nucleation process. [5][6][7][8] Poly(lactic acid) (PLA) is a biosourced polymer.…”
Section: Introductionmentioning
confidence: 99%